Suspensions control processes in Eastern Europe from iconoclasm to cybernetics - Velminski, Wladimir 1976- (Peter Lang, 2018)
suspension, n. [1] 1. the act of suspending. 2. the state of being suspended. 3. temporary abrogation or withholding, as of a law, privilege, decision, belief, etc. 4. stoppage of payment of debts or claims because of financial inability or insolvency. 5. Chem. a. the state in which the particles of a substance are mixed with a fluid but are undissolved. b. a substance in such a state. 6. Physical Chem. a system consisting of small particles kept dispersed by agitation (mechanical suspension) or by the molecular motion in the surrounding medium (colloidal suspension)